Stakeholder priorities for ART initiation and early retention strategies in Malawi: a qualitative study comparing international and national perspectives - Santhi Hariprasad; Khumbo Phiri; Marguerite Thorp; Katherine Holland; Rose Nyirenda; Sundeep Gupta; Sam Phiri; Lora L. Sabin; Kathryn Dovel (BMC Public Health)
Abstract Introduction New or returning antiretroviral therapy (ART) clients are largely ineligible for differentiated service delivery (DSD) models. These clients are at increased risk of treatment interruption and may benefit from flexible care models, but stakeholder buy-in may limit progress on interventions for this population. We qualitatively explored stakeholder perceptions and decision-making criteria for scaling DSD models for new or returning ART clients in Malawi. Methods We conducted in-depth interviews with internationally-based stakeholders (from foundations, multilateral organizations, and non-governmental organizations (NGOs)) and Malawi-based stakeholders (from the Malawi Ministry of Health and local implementing partners). Interviews included two think-aloud scenarios in which participants rated and described their perceptions of (1) the relative priority of five criteria (cost, effectiveness, acceptability, feasibility, and equity) in determining which interventions to implement for new or returning ART clients and (2) the relative priority of seven potential interventions (monetary incentives, non-monetary incentives, community-based care, ongoing peer/mentor support and counseling, eHealth, facility-based interventions, and multi-month dispensing) for the same population. Interviews were completed in English via video conference and were audio-recorded. Transcriptions were coded using ATLAS.ti version 9. We examined the data using thematic content analysis and explored differences between international and national stakeholders. Results We interviewed twenty-two stakeholders between October 2021-March 2022. Thirteen were based internationally and nine were based in Malawi. Both groups prioritized client acceptability, but diverged on other criteria: international stakeholders prioritized effectiveness and Malawi-based stakeholders prioritized cost, feasibility, and sustainability. Both stakeholder groups were most interested in facility-based DSD models such as multi-month dispensing and extended facility hours. Nearly all stakeholders described person-centered care as a critical focus to incorporate into all DSD models. Conclusions National and international stakeholders support DSD models for new or returning ART clients. Client acceptability and sustainability should be prioritized to address the concerns of nationally-based stakeholders. Future studies should explore reasons for differences in national and international stakeholders’ priorities and how to ensure that local perspectives are incorporated into funding and programmatic decisions.